Conjugated microporous polymers with excellent electrochemical performance for lithium and sodium storage. Issue 5 (22nd December 2014) - Zhang, Shengliang; Huang, Wei; Hu, Pu; Huang, Changshui; Shang, Chaoqun; Zhang, Chuanjian; Yang, Renqiang; Cui, Guanglei
Abstract : Conjugated microporous polymers are explored as high-performance electrode materials for lithium and sodium storage, exhibiting excellent electrochemical performance. Abstract : Conjugated microporous polymers, which exhibit high specific capacity, superior cycle stability and remarkable rate capability, are explored as high-performance electrode materials for lithium and sodium storage. Their excellent electrochemical performance can be attributed to their conductive frameworks, plentiful redox-active units, high specific surface area and homogeneous microporous structure.